The Pentagon Papers as History - Stephen J. Whitfield (Revue LISA, 2022)
This article examines the most consequential Constitutional case in American history regarding the right of the press to expose the origins of a war – while it was still being fought. The crisis of the early summer of 1971 was unprecedented. In the past, for the sake of national security, limitations had sometimes been imposed on newspapers and magazines condemning the war that was being fought – most notoriously, in the twentieth century, during the First World War. But the case of the Pentagon Papers was peculiar, because the New York Times, and soon the Washington Post, and then about two dozen other daily newspapers reprinted top secret documents that the press was not authorized to possess. The Supreme Court therefore had to resolve the conflict between the claims of the press under the seemingly unambiguous First Amendment (“Congress shall make no law . . .”) and the warning of the executive branch that the lives of American servicemen in Indochina were at stake because of the most enormous leak of secret government documents ever. The Pentagon Papers represent a revealing episode in the history of journalism, the history of governance and the history of jurisprudence.